An Aramaic approach to the Gospels and Acts - Black, Matthew (Peabody, MA Hendrickson, 1967)
Includes bibliographical references and indexes.
First edition published 1946. Introduction by Craig A. Evans included in1998 reprint of 3rd ed .
Keywords: Bible. N.T. Gospels -- language, style; Bible. N.T. Acts -- language, style